2014
DOI: 10.1002/ijc.28839
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin regulates NF-κB activityviaTNFRSF19 in colorectal cancer cells

Abstract: Wnt/b-catenin signaling plays a crucial role in the regulation of colon tissue regeneration and the development of colon tumors. Under physiological conditions, b-catenin activity is tightly controlled. However, the majority of sporadic forms of colorectal cancer are characterized by inactivation of the tumor suppressor gene APC due to loss of heterozygosity (LOH), resulting in deregulation of the protein b-catenin. Apart from known b-catenin target genes like MYC, OPG, and DKK4, the gene TNFRSF19, a member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 35 publications
3
58
1
Order By: Relevance
“…Regarding the prognostic significance of TROY, one research group reported no increase in TROY mRNA in CRC specimens in a small sample of patients (n=20) (13). In contrast, another group reported an increase in TROY mRNA expression in 4 of 8 CRC tissues but did not investigate its prognostic significance (17). Because the number of samples analyzed in both reports was small, they were insufficient to evaluate the prognostic significance of the expression level of TROY.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the prognostic significance of TROY, one research group reported no increase in TROY mRNA in CRC specimens in a small sample of patients (n=20) (13). In contrast, another group reported an increase in TROY mRNA expression in 4 of 8 CRC tissues but did not investigate its prognostic significance (17). Because the number of samples analyzed in both reports was small, they were insufficient to evaluate the prognostic significance of the expression level of TROY.…”
Section: Discussionmentioning
confidence: 98%
“…One research group reported that TROY is significantly up-regulated in neoplastic tissues from mice during intestinal tumorigenesis and is produced specifically by fast-cycling intestinal stem cells (13). Another research group suggested that TROY can contribute to the initiation or progression of colorectal tumors with deregulated β-catenin activity (17). Regarding the prognostic significance of TROY, one research group reported no increase in TROY mRNA in CRC specimens in a small sample of patients (n=20) (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Wnt/ -catenin signaling plays a critical role in the regulation of colon tissue regeneration and the development of colon cancer (Schon et al, 2014), the expression of Wnt/ -catenin signaling proteins were assessed after exposure to ellagic acid. The expression of -catenin was decreased significantly in HT29 and in HCT 116 cells treated with ellagic acid, however a marked increase in the expression of p--catenin levels was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer carcinogenesis has been reported to be associated with genetic errors in genes involved in apoptosis and cell proliferation (Davies et al, 2005;Watson, 2006;Damaschke et al, 2013;Bharati et al, 2014). Genetic defects triggering aberrant activation of Wnt/ -catenin signalling are common and are reported in over 90% of sporadic cases of colon cancer (Miyaki et al, 1994;Clevers, 2006;Klaus and Birchmeier, 2008;Schon et al, 2014). The key effecttor of Wnt/ -catenin signaling pathway is -catenin that upon activation of Wnt signal, translocates into the nuclear region forming a ternary complex with transcription factors-TCF/Lef (T-cell factor, lymphoid enhancer factor) and activates genes involved in cell pro- Studies have demonstrated that phytochemicals are effective in modulating Wnt/ -catenin signalling pathway (Zhang, et al, 2013;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%